Gender Memoderasi Pengaruh Love of Money Terhadap Tax Evasion Tendency - Sari, Maria Mediatrix Ratna; Wirajaya, I Gde Ary; Supadmi, Ni Luh (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.2, Agustus 2019 (pp. 111-247)DO - 10.24843/JEKT.2019.v12.i02.p08, 2019)
The purpose of this study was to examine the effect of love of money on tax evasion tendency with gender as moderating. The population in this study is the Udayana University Masters of Accounting. Sample selection with nonprobability sampling method with purposive sampling technique, obtained 184 respondents. Data collection using a questionnaire. Data were analyzed using Moderated Regression Analysis (MRA). The results show that love of money has a positive effect on tax evasion tendency, and gender is able to moderate the effect of love of money on tax evasion tendency. This study provides evidence and empirical support from tax moral theory and gender role theory related to ethical views on tax evasion tendency, the nature of love of money and gender as moderating.